Cytogenotoxicity and safe doses of Azadirachta indica L. (Neem tree) leaf extract obtained in Birnin Kebbi, Nigeria - Tajudeen Yahaya; Salisu Titilola Fausat; Angela Daniel; Muhammed Ndakogi Musa; Emmanuel John; Ridwan Sulaiman; Abubakar Saadu; ThankGod James (Ruhuna Journal of Science)
Azadirachta indica (neem tree) is used to treat diseases in Nigeria, however, scarcity of documented information on the plant's toxicity exists in the country. Toxicity evaluation of medicinal plants in relation to geographical location is essential, as toxicity may vary due to differences in pollutants and environmental factors. This study assessed the phytochemical composition, heavy metal content, cytotoxic potential, and safe doses of methanolic leaf extracts of A. indica obtained from Birnin Kebbi, Nigeria. Twenty-one Allium cepa bulbs were divided equally into seven groups. The negative control (Group 1) and positive control (Group 2) bulbs were grown for five days over beakers containing distilled water and formaldehyde, respectively. Test groups (Groups 3–7) were grown over beakers containing A. indica extract solutions at concentrations of 0.25, 0.5, 1.0, 2.0, and 4.0 g, respectively. Phytochemical analysis revealed abundant flavonoids, phenols, and saponins, moderate levels of tannins, and trace amounts of quinones, cardiac glycosides, and terpenoids. Heavy metal analysis showed the presence of copper (3.8 mg/kg), lead (0.12 mg/kg), and cadmium (0.04 mg/kg), all of which exceeded the permissible limits established by WHO. Except for the 0.25 g group, the test groups exhibited dose-dependent (p ≤ 0.05) cytogenetic effects, including reduced root growth and mitotic index. Chromosomal abnormalities such as sticky, bridged, vagrant, laggard, and fragmented chromosomes were also observed. These findings suggest that A. indica may be safe at low concentrations but exhibits toxic effects at higher concentrations. The results provide a valuable baseline for further investigations into the plant's safety.